Increased Hepatic Fibrinogen Bβ-gene Transcription Is not enough to Increase Plasma Fibrinogen Levels - Rezaee, F.; Maas, A.; Verheijen, J. H.; Koopman, J. (Thrombosis and Haemostasis, 2001)
The fibrinogen Aα, Bβ, and γ polypeptides are encoded by three separate genes, which are arranged in the order γ-α-β. In order to study the biosynthesis of fibrinogen in vivo we generated a line of transgenic mice carrying extra copies of the fibrinogen β-gene. To clone the mouse fibrinogen Bβ-chain gene, a mouse 129 Sv/Ev genomic cosmid library was screened, using the mouse fibrinogen Aα-, Bγ-chain cDNA. A clone containing the complete fibrinogen Bβ-chain gene including approximately 11-kb of the natural promoter region was identified and subsequently microinjected into mice. Southern blot analysis identified a founder that carried additional copies of the fibrinogen Bβ-chain gene. Transgenic offspring of this founder were interbred and heterozygous and homozygous transgenic mice were obtained. Northern blot analysis demonstrated approximately a 3-fold increase in fibrinogen Bβ mRNA in heterozygous mice as compared to wild-type, whereas homozygous transgenic mice showed approximately a 9-fold increase. The levels of the Aα and γ mRNAs in transgenic homozygous mice were not changed as compared to those in wild-type mice. Fibrinogen levels in plasma were not significantly increased in transgenic mice as compared to wild-type mice.These results indicate that: additional copies of the fibrinogen Bβ-chain gene lead to increased levels of the Bβ-chain mRNA in the liver; the increased levels of Bβ-chain mRNA in homozygous overexpression mice do not change the transcription levels of the two other fibrinogen mRNAs in vivo; the absence of an increased plasma fibrinogen level in the transgenic mice indicates that this level is not regulated solely by transcription of the Bβ-chain gene.
Keywords: Fibrinogen transcription; regulation Bβ-gene